(untitled) (Voice of Teacher, 2022)
Gender based violence was measured based on different questions related to physical violence, emotional violence and sexual violence. The questions were asked to the Bachelor and Masters Level students. Nepal Demographic and Health Survey (NDHS) questionnaires were taken as reference for questionnaire development. This study entitled “Causes and Consequences of Gender Based Violence against College Girls” is based on the study of Bachelor and Masters Level students of Padmakanya Multiple Campus, Kathmandu. The objectives of the study was to identify the causes and consequences of gender based violence of college students. In this study cross-sectional research design was applied. The Study followed the quantitative approach. From this study it was found that about 34.3percent of the respondents were experienced violence in their life time. Out of the total case of the emotional violence, more than one fifth (24.2%) were humiliate in front of others followed by insulted or make feel bad (20.6%)and threaten to hurt or harm by someone (13.6%). Respondents who were experienced physical violence, highest percentage (10.6%) were pushed, shook and throw something on her followed by twist arm or pull hair (6.1%),slapped and punched (4.5%), and kicked, dragged and beaten (3.8%).A few of the respondents have experienced the sexual violence (12.1%). Among them, 6.1 percent of the respondents were physically force to perform any other sexual acts followed by physically forced to have sexual intercourse(4.5%) and threatened to perform sexual acts in any other way (1.5%).